2007
DOI: 10.1007/s11832-007-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with congenital clasped thumb: A prospective study of 40 patients with the results of treatment

Abstract: Purpose Congenital clasped thumb is a deformity that is associated with heterogeneous congenital anomalies and it has been addressed in many congenital syndromes. The aim of this study was to diagnose and evaluate cases of clasped thumb as regards the associated congenital anomalies and syndromes, and evaluation of the results of treatment of such cases. Methods A prospective study on 40 patients with 73 clasped thumbs was done. All the patients' data regarding their personal, family, pregnancy and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 26 publications
1
49
1
Order By: Relevance
“…Treatment of congenitally clasped thumb depends on disease stage, age at presentation, and comorbid pathologies. 10 , 12 Tsuyuguchi et al 12 reported that good results were achieved with type I and type II cases with conservative methods. In type II and type III, cases in whom conservative treatment is ineffective surgical treatment produces good results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment of congenitally clasped thumb depends on disease stage, age at presentation, and comorbid pathologies. 10 , 12 Tsuyuguchi et al 12 reported that good results were achieved with type I and type II cases with conservative methods. In type II and type III, cases in whom conservative treatment is ineffective surgical treatment produces good results.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical methods are not recommended for patients who have agenesis or severe hypoplasia of EPB. 14 , 15 Ghani et al 10 reported that conservative treatment was effective for patients under 1 year of age but then, and in type II and type III patients who do not respond to conservative treatment surgery gives better results. Lin et al 9 suggested that application of a splint will give successful results in patients under 1 year of age, who have neither skin contracture at first evaluation nor absence or severe weakness of EPB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations